The Influence of Word of Mouth (WOM) and Price Towards The Decision for Attending College at XY School of Tourism - Enos Julvirta Sinuraya; Tridjoko Sulistio; Albella Desta (Enrichment : Journal of Management, 2021)
This research was conducted with the aim of knowing the effect of word of mouth (X1) and price (X2) on the purchase decision (Y) of students to continue their study at XY School of Tourism. This research model uses quantitative descriptive analysis with regression methods using SPSS build tools 1.0.0.1347 for MAC. It used a total sample of 83 participants with a purposive sampling technique and was measured by a questionnaire consisting of 34 statements. Its results showed that word of mouth (X1) and price (X2) affect purchasing decisions (Y) either partially or simultaneously. The results of this study found that word of mouth (X1) influences purchasing decisions (Y) by 49 percent meanwhile the price (X2) affects purchase decision (Y) for as much as 39.4 percent, and the rest is influenced by other variables.